Building a Workforce for Future Health Systems: Reflections from Health Policy and Systems Research. (24th May 2018) - Javadi, Dena; Tran, Nhan; Ghaffar, Abdul
Abstract : Introduction: The era of the Sustainable Development Goals calls for multidisciplinary research and intersectoral approaches to addressing health challenges. This presents a unique opportunity for multidisciplinary fields concerned with complex systems. Those working in system‐oriented fields such as health policy and systems research (HPSR) and health services research must be forward‐thinking in optimizing their collective ability to address these global challenges. Objectives: The objective of this commentary was to share reflections on challenges and strategies in managing the HPSR workforce in order to stimulate dialogue and cross‐learning across similar fields. Strategies/Findings: The following strategies are discussed here: definitional clarity of expected competencies and coordination across HPS researchers, national investment in HPSR, institutional capacity for coproduction of knowledge across different types of actors, and participatory leadership. Conclusions: Creative approaches in training, financing, developing, and leading the diverse workforce required to strengthen health systems can pave the way for its full‐time and part‐time members to work together.